Emergency Coagulation Assessment During Treatment With Direct Oral Anticoagulants: Limitations and Solutions. Issue 9 (September 2017) - Ebner, Matthias; Birschmann, Ingvild; Peter, Andreas; Härtig, Florian; Spencer, Charlotte; Kuhn, Joachim; Blumenstock, Gunnar; Zuern, Christine S.; Ziemann, Ulf; Poli, Sven
Abstract : Background and Purpose—: In patients receiving direct oral anticoagulants (DOACs), emergency treatment like thrombolysis for acute ischemic stroke is complicated by insufficient availability of DOAC-specific coagulation tests. Conflicting recommendations have been published concerning the use of global coagulation assays for ruling out relevant DOAC-induced anticoagulation. Methods—: Four hundred eighty-one samples from 96 DOAC-treated patients were tested using prothrombin time (PT), activated partial thromboplastin time (aPTT) and thrombin time (TT), DOAC-specific assays (anti-Xa activity, diluted TT), and liquid chromatography–tandem mass spectrometry. Sensitivity and specificity of test results to identify DOAC concentrations <30 ng/mL were calculated. Receiver operating characteristic analyses were used to define reagent-specific cutoff values. Results—: Normal PT and aPTT provide insufficient specificity to safely identify DOAC concentrations <30 ng/mL (rivaroxaban/PT: specificity, 77%/sensitivity, 94%; apixaban/PT: specificity, 13%/sensitivity, 94%, dabigatran/aPTT: specificity, 49%/sensitivity, 91%). Normal TT was 100% specific for dabigatran, but sensitivity was 26%. In contrast, reagent-specific PT and aPTT cutoffs provided >95% specificity and a specific TT cutoff enhanced sensitivity for dabigatran to 84%. For apixaban, no cutoffs could be established. Conclusions—: Even if highly DOAC-reactive reagents are used, normal results of global coagulation tests are not suited to guide emergency treatment: whereas normal PT and aPTT lack specificity to rule out DOAC-induced anticoagulation, the low sensitivity of normal TT excludes the majority of eligible patients from treatment. However, reagent-specific cutoffs for global coagulation tests ensure high specificity and optimize sensitivity for safe emergency decision making in rivaroxaban- and dabigatran-treated patients. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifiers: NCT02371044 and NCT02371070. Abstract : Supplemental Digital Content is available in the text.